Multi-Piston briquetting technology for West Africa - CGIAR Research Program on Rice (2021)
The components of the technology have been fabricated, tested and validated with key stakeholders in Cameroon, Benin and Cote d’Ivoire. This technology targets young small-scale processors of agricultural waste such as rice husk. Technical drawings of the equipment have been prepared and publicly available.